Predicting the habitat suitability of Ilex verticillata (Aquifoliaceae) in China with field-test validations. - Yawen Yin; Zhaobin Hou; Qiuyue Sun; Bailing Zhu; Jiaqi Liu; Yiping Zou; Mingzhuo Hao (PLoS ONE)
The cut branches of Ilex verticillata are highly ornamental and have high economic value. Since its introduction to China, it has received widespread attention. In the context of climate change today, ensuring its promotion and sustainable production in China is of great significance. In this study we evaluated the habitat suitability of the species using MaxEnt, combined with climate and soil variables, to assess the impact of climate change on its potential suitable habitat. We used 121 I. verticillata occurrence data and validated the model prediction using extensive field testing (12 test sites located in areas from 23.19° N to 42.91° N and 76.17° E to 125.14° E). The habitat suitability model (AUC = 0.854) performed well. Among them, three precipitation variables and one temperature variable were the main factors determining the distribution of I. verticillata in China. Field trial tests and model predictions of the suitability of I. verticillata were consistent, indicating that our model predictions are biologically meaningful and economically valuable. Under the Shared Socioeconomic Pathways (SSPs) climate change scenario, the high and medium suitable habitats for this species will be reduced in the future climate. This study helps to better understand the impact of climate change on I. verticillata and provides suggestions for the introduction and cultivation areas and protection of this species in China.